Pengaruh status gizi & asupan gizi ibu terhadap berat bayi lahir rendah pada kehamilan usia remaja - Retni, Retni; Margawati, Ani; Widjanarko, Bagoes (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Introduction. Teenage pregnancy at risk of having a baby with low birth weight (LBW). This happens because of the condition of the mother is still in the growth, physical development is not perfect so it can be detrimental to the health of mother and fetus. The research objective is to analyze the effect of nutritional status and nutrient intake of mothers of low birth weight in pregnancy adolescence.Methods:Â The study design was observational with prospective cohort approach.The subject is the population of third trimester pregnant women aged 16-19 years amounted to 27 people. The nutritional status measured by antropometry. Nutrient intake was measured by 24-hour food recall method. Data were analyzed by calculating the relative riskResults: 66,7% had a protein energy malnutrition, 51,9% had less weight gain during pregnancy, and 59,3% are anemic. The mean intake of energy, protein, folic acid, iron, zinc, vitamin A and C are in not enough categories. The relative risk test showed that less weight gain during pregnancy (RR= 3,71;95% CI 1,34-10,25, low energy intake (RR =6.03; 95% CI 5,68-898,64), low protein (RR= 13,00;95% CI 1,97-85,45), low folic acid (RR = 13,00;95% CI 1,97-85,45), low iron (RR= 4,00;95% CI 1,71-9,34) at risk of having low birth weight. Conclusions: Pregnant women-adolescence with less weight gain during pregnancy, energy protein malnutrition and low energy, protein, folic acid and iron intake at risk of having low birth weight.